Degradation of mechanical properties of bovine cortical bone during long-term whole bone storage. - Carstens, Lia (Department of Mechanical Engineering, 2025)
Understanding the mechanical properties and behaviour of bone is critical for predicting fractures and failures in the human skeletal system. Mechanical testing has been the conventional method for characterizing bone materials. However, due to the limited wall thickness of whole bones, only small cortical bone specimens can be obtained which creates challenges when accurate modulus measurements are required. Large-scale universal testing machines often introduce global compliance errors that obscure precise displacement data, in addition to localized compliance at the specimen-platen interface. These compliance effects are especially acute when conducting tests on quasi-brittle materials like cortical bone, that exhibit low failure strains. A thorough review of existing literature shows that there is a gap regarding the storage protocols for bone specimens prior to mechanical testing. While storage methods are generally well described, important parameters such as the interval between donor death and bone retrieval, or the time between specimen preparation and testing, are seldom reported. As bone degrades after removal from the donor, understanding this degradation is crucial to determining the duration that stored specimens remain representative of in-vivo conditions. This dissertation investigates the effects of long-term storage on the mechanical properties of bovine cortical bone, comparing two protocols: "machined-frozen" (MF) and "frozen-machined" (FM). While degradation was observed in both cases, FM samples retained their mechanical integrity slightly better than machined specimens. The elastic moduli for both groups were at the lower end of expected values after one month of storage, with a significant decline by the third month. The work described above required the development of specialized testing techniques. In particular, this work addresses compliance errors by utilizing a micronaccurate sub-press equipped with novel frustum platens designed to centralize and uniformly distribute loads. These platens, enabled precise theoretical and experimental evaluations of localized compliance, ensuring accurate modulus measurements for small specimens. Validation was achieved by comparing results from compressive tests on cylindrical polymethyl methacrylate (PMMA) and aluminium (Al) specimens of varying heights against three alternative methods i.e. stress wave propagation, tensile extension, and three-point bending, each of which typically require larger specimens. A high degree of correlation between the methods demonstrates the accuracy and utility of this approach in small-specimen testing.